Monocyte signature as a predictor of chronic lung disease in the preterm infant - Windhorst, Anita C.; Heydarian, Motaharehsadat; Schwarz, Maren; Oak, Prajakta; Förster, Kai; Frankenberger, Marion; Gonzalez Rodriguez, Erika; Zhang, Xin; Ehrhardt, Harald; Hübener, Christoph; Flemmer, Andreas W.; Hossain, Hamid; et al. (Frontiers in Immunology, 2023)
Introduction Inflammation is a key driver of morbidity in the vulnerable preterm infant exposed to pre- and postnatal hazards and significantly contributes to chronic lung disease, i.e. bronchopulmonary dysplasia (BPD). However, the early changes in innate immunity associated with BPD development are incompletely understood. Methods In very immature preterm infants below 32 weeks gestational age (GA; n=30 infants), monocyte subtypes were identified by Flow Cytometry at birth and throughout the postnatal course including intracellular TNF expression upon LPS stimulation. Complementing these measurements, cytokine end growth factor expression profiles (Luminex® xMAP®; n=110 infants) as well as gene expression profiles (CodeLinkTM Human I Bioarray; n=22) were characterized at birth. Results The abundance of monocyte subtypes differed between preterm and term neonates at birth. Specifically, CD14++CD16+ (intermediate) monocytes demonstrated a dependency on PMA and elevated levels of nonclassical (CD14+CD16++) monocytes characterized preterm infants with developing BPD. Postnatally, lung injury was associated with an increase in intermediate monocytes, while high levels of nonclassical monocytes persisted. Both subtypes were revealed as the main source of intracellular TNF-α expression in the preterm infant. We identified a cytokine and growth factor expression profile in cord blood specimen of preterm infants with developing BPD that corresponded to the disease-dependent regulation of monocyte abundances. Multivariate modeling of protein profiles revealed FGF2, sIL-2 Rα, MCP-1, MIP1a, and TNF-α as predictors of BPD when considering GA. Transcriptome analysis demonstrated genes predicting BPD to be overrepresented in inflammatory pathways with increased disease severity characterized by the regulation of immune and defense response pathways and upstream regulator analysis confirmed TNF-α, interleukin (IL) -6, and interferon α as the highest activated cytokines in more severe disease. Whereas all BPD cases showed downstream activation of chemotaxis and activation of inflammatory response pathways, more severe cases were characterized by an additional activation of reactive oxygen species (ROS) synthesis. Discussion In the present study, we identified the early postnatal presence of nonclassical (CD14+CD16++) and intermediate (CD14++CD16+) monocytes as a critical characteristic of BPD development including a specific response pattern of monocyte subtypes to lung injury. Pathophysiological insight was provided by the protein and transcriptome signature identified at birth, centered around monocyte and corresponding granulocyte activation and highlighting TNFα as a critical regulator in infants with developing BPD. The disease severity-dependent expression patterns could inform future diagnostic and treatment strategies targeting the monocytic cell and its progeny.